Crafting Fetish Across Materials and Sexual Styles: An Interview with Skeeter of Mr. S Leather. (3rd May 2020) - Cubbin, Tom
Abstract: This statement of practice sees Skeeter of Mr. S Leather in San Francisco in conversation with Tom Cubbin about the role of craftsmanship in the development of products sold within the gay leather and fetish scenes. In her thirty years at Mr. S, Skeeter has fostered craft and making practices that have expanded from leather aimed primarily at gay men, to a multi-material business that caters to ever wider forms of kink and fetish practices. The discussion explores how new products are developed, produced and quality-tested in relation to broader leather and kink communities. Skeeter also shares her experiences of her journey from the women's kink community in London to running the production, research and development at one of the largest producers of male bondage and fetish gear.